Measurement of Dielectric Constant Îµâ of Fe73.5-Cu1- Ta3-Si13.5-B9 Biphase Metallic glass - Ahsan, MZ; Khan, FA (Journal of Bangladesh Academy of Sciences, 2009)
doi: 10.3329/jbas.v32i1.2448 Journal of Bangladesh Academy of Sciences, Vol. 32, No. 1, 107-109, 2008